Investigating the contribution of ventral-lexical and dorsal-sublexical pathways during reading in bilinguals - Bakhtiari, Reyhaneh; Boliek, Carol; Cummine, Jacqueline (Frontiers in Human Neuroscience, 2014)
Several studies suggest the existence of ventral-lexical and dorsal-sublexical systems for reading. The relative contribution of these pathways can be manipulated by stimulus type and task demands. However little is known about how bilinguals use these systems to read in their second language. In this study diffusion tensor imaging was used to investigate the relationship between white matter integrity and reaction time in a group of 12 Chinese-English bilingual and 11 age-matched English monolingual adults. Considering a dual-route model of reading, the following four tracts were isolated in both the left and right hemispheres using a tractography measurement approach. Ventral tracts included the uncinate fasciculus (UF) and the inferior longitudinal fasciculus (ILF). The dorsal tracts of interest were the arcuate fasciculus (AF) and the superior longitudinal fasciculus (SLF). A significant correlation between the reaction time in a reading task and the mean diffusivity (MD) value was observed in the right UF in both bilingual and monolingual groups. Moreover, in the bilingual group we observed significantly more positive relationships between reaction time and MD in the right AF, and bilaterally in the SLF. We concluded that the relative contribution of the dorsal system for reading is greater in bilinguals than monolinguals. Further, these findings implicate a role of the right hemisphere in reading.